Desempenho de novilhas de corte para acasalamento aos 14 meses de idade - Alves, Marcos Bernardino (2014)
Performance of beef heifers grazing ryegrass (Lolium multiflorum Lam.) was studied exclusively with animals grazing, receiving grain corn, or whole oat grain at the level of 0.93% of body weight. The supplement was offered daily at 14 hours. The grazing was continuous with a variable number of animals. The experimental design was completely randomized with repeated measures, three feeding systems and nine replicates, each animal being considered an experimental unit. Supplementation with or without use of corn or oat grazing ryegrass reproductive development allows for the heifers are bred at 14 months of age.